2014
DOI: 10.1039/c4ta01062k
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis and characterization of chalcopyrite CuInS2 nanoparticles

Abstract: We synthesized tetragonal chalcopyrite CuInS2 (CIS) nanoparticles from molecular single source precursors, (Ph3P)2Cu-(μ-SEt)2In(SEt)2, by a one-pot reaction in the presence of 3-mercaptopropionic acid at reaction times of 3 hours or less with high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Coincided with chalcopyrite CuInS 2 , the absorption band gap of as-synthesized CuInS 2 QDs was calculated to be about 1.75 eV, which matches well with the energy band gap requirements. 37 The TiO 2 -NAs show a wide shoulder in the region of 300–360 nm, which is in good agreement with the previous work (Figure 1b). 38 The strong peak at the wavelength of 310 nm is based on Ti (3d)–O (2p) energy transition of TiO 2 nanoarrays.…”
Section: Resultssupporting
confidence: 93%
“…Coincided with chalcopyrite CuInS 2 , the absorption band gap of as-synthesized CuInS 2 QDs was calculated to be about 1.75 eV, which matches well with the energy band gap requirements. 37 The TiO 2 -NAs show a wide shoulder in the region of 300–360 nm, which is in good agreement with the previous work (Figure 1b). 38 The strong peak at the wavelength of 310 nm is based on Ti (3d)–O (2p) energy transition of TiO 2 nanoarrays.…”
Section: Resultssupporting
confidence: 93%
“…Similarly to Cd-and Pb-based NPs, the CIS NPS can be stabilized in polar media by small mercapto carboxylic acids. [25][26][27][28][29] For example, water-soluble Cu-In-S NPs covered with a ZnS shell (CIS@ZnS) with a PL quantum yield of up to 40% were produced by the microwave heating using a combination of mercaptoacetic acid (MAA, HSCH 2 COOH) and sodium citrate as capping agents. 27 A relatively mild synthesis of mercapto acetate-stabilized CIS NPs at 90-120 C was reported in ref.…”
Section: Introductionmentioning
confidence: 99%
“…26 A synthesis of MPA-capped CIS NPs by decomposition of a single molecular precursor in the N 2 atmosphere and liquid MPA was also reported. 29 It should be noted, that in the solar cells with the TiO 2 /CIS photoanodes the presence of an additional -CH 2 À group in the MPA stabilizer molecule as compared with MAA introduces additional distance between the donor (CIS) and acceptor (TiO 2 ) that may be detrimental to the solar cell performance. Probably, the highest efficiency to date, 7.04%, was reported in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Among the lower‐temperature routes, Hepp and co‐workers used a single molecular source and found that the synthesis mainly resulted in intermediate precursors such as Cu x S y and In x S y without the formation of the CIS phase 44. Certain starting precursors such as (Ph 3 P) 2 Cu(μ‐SEt) 2 In(SEt) 2 have been suggested for the formation of the CIS phase at temperatures as low as 150 °C 45…”
Section: Resultsmentioning
confidence: 99%